PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DAERAH KABUPATEN SORONG - Amelia Krar; Andrey Maryen; Ade Andriani Renouw (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The state civil apparatus is the driving force for activities within an agency, in carrying out activities employees need work instructions from the agency so that their implementation is in accordance with the plan and must be supported by agency work regulation so as to create work discipline. In this case there is also something that must be considered by the agency, namely regarding the performance of employees. Employee performance must be considered because it is one of the keys to success. This study aims to determine the magnitude of the effect of work discipline on the performance of employees at the office of the education and training personnel agency sorong regency. The population of this study was the entire staff of the education and training agency office in sorong regency totaling 60 people, and a sample of 52 people was taken. Data collection was carried out using questionnaires and interviews and observation. While the method used in this study was quantitative. The results of this study indicate that work discipline has a positive and significant effect on employee performance at the regional education and training personnel agency office in sorong regency.